PEMANFAATAN SISTEM INFORMASI KERUGIAN NEGARA/DAERAH DALAM PENYELESAIAN KERUGIAN NEGARA PADA AUDITORAT KEUANGAN NEGARA VI BPK RI (Studi Kasus Satuan Kerja di Lingkungan Kemendikbudristek) - Makhi, Anang Hajarul; Akbar, Bahrullah; Karno, Karno (Journal of Economic, Bussines and Accounting (COSTING), 2024)
State / Regional Loss Information System used in the management of monitoring the settlement of state / Regional losses or SIKAD, starting from the stage of determining monitoring procedures, managing documentation and follow-up status on the results of monitoring the settlement of state/Regional losses, to the implementation of monitoring the settlement of state/regional losses. In the utilization of SIKAD, there are still obstacles that occur and have not been able to optimally increase the settlement of state losses. This research uses descriptive qualitative research methods, which will describe and analyze the utilization of SIKAD with data collection techniques through interviews, observation, and documentation, at AKN VI BPK RI. The purpose of the study was to determine utilization, analyze inhibiting factors and efforts to resolve inhibiting factors, in the utilization of SIKAD so as to increase the number of settlements of state losses. The results of the research on the Utilization of the State / Regional Loss Information System in the settlement of state losses at AKN VI BPK RI using the theory of basic models and basic activities in information systems by George M. Marakas and O'Brien are quite useful in helping to carry out the process of monitoring and management up to the process of resolving cases of state losses. However, in the implementation of SIKAD utilization, there are still obstacles in human resources, data completeness, internet networks, data resource input, data processing, information product output, and system work control. Efforts that can be made by AKN VI BPK RI, namely, conducting socialization, reconciling data between SIKAD and SIPTL, coordinating data completeness, increasing bandwidth resources for Virtual Private Network (VPN) access, adjusting output results, making technical guidelines, guidelines, or procedures, and improving and adding features that are still lacking.